ONE – STAGE METAL WASTES RECYCLING - S. L. Rovin; L. E. Rovin; V. A. Zharanov; T. M. Zayats (Литьë и металлургия)
Rotary tilting furnace is the most efficient installation for recycling of dispersible metal wastes of any alloy. Several constructions have been designed for chips heating and melting, scale recovery, ets.